Relationships Between Gastrointestinal Parasite Infections and the Fecal Microbiome in Free-Ranging Western Lowland Gorillas - Vlčková, Klára; Pafčo, Barbora; Petrželková, Klára J.; Modrý, David; Todd, Angelique; Yeoman, Carl J.; Torralba, Manolito; Wilson, Brenda A.; Stumpf, Rebecca M.; White, Bryan A.; Nelson, Karen E.; Leigh, Steven R.; et al. (Frontiers in Microbiology, 2018)
Relationships between gastrointestinal parasites (GIPs) and the gastrointestinal microbiome (GIM) are widely discussed topics across mammalian species due to their possible impact on the host's health. GIPs may change the environment determining alterations in GIM composition. We evaluated the associations between GIP infections and fecal microbiome composition in two habituated and two unhabituated groups of wild western lowland gorillas (Gorilla g. gorilla) from Dzanga Sangha Protected Areas, Central African Republic. We examined 43 fecal samples for GIPs and quantified strongylid nematodes. We characterized fecal microbiome composition through 454 pyrosequencing of the V1-V3 region of the bacterial 16S rRNA gene. Entamoeba spp. infections were associated with significant differences in abundances of bacterial taxa that likely play important roles in nutrition and metabolism for the host, besides being characteristic members of the gorilla gut microbiome. We did not observe any relationships between relative abundances of several bacterial taxa and strongylid egg counts. Based on our findings, we suggest that there is a significant relationship between fecal microbiome and Entamoeba infection in wild gorillas. This study contributes to the overall knowledge about factors involved in modulating GIM communities in great apes.